Determinan Indeks Pembangunan Manusia di Klaster Daerah Cepat Maju dan Cepat Tumbuh di Provinsi Jawa Timur - Indah Purnama Sari; Zaeni Miftah (Sosio e-Kons, 2021)
This study examines the determinants of HDI in Fast-Developing and Fast-Growing Regions. The research was carried out in 2020 in East Java Province, by previously dividing East Java into four regional categories, namely Fast Forward and Fast-Growing Areas, Fast Developing Areas, Developed But Depressed Areas, and Relatively Disadvantaged Areas. This study used a cluster analysis research design and comparative causal analysis. HDI determinants analyzed include variables: unemployment, Gini ratio, and population density. The number of samples used was 66-panel data samples from 11 districts/cities with cross-section data and 6 years of time-series data. The data used are secondary data from East Java BPS, then analyzed by panel data regression method. The findings of the study are that in the Fast-Developing and Fast-Growing Areas, unemployment, Gini ratio, and population density simultaneously have a significant effect on HDI; unemployment has a significant negative effect on HDI; Gini ratio has a significant positive effect on HDI, and population density has a significant positive effect on HDI.